Traditional Tutoring and Peer Tutoring: Ethical Aspects - Anna Izabela Brzezińska; Karolina Appelt (University of Lower Silesia, 2013)
The authors of the article indicate a variety of ethical issues concerning the functions of tutoring in education, both the traditional as well as peer tutoring. They claim that, the basic condition for ethical, and yet effective, tutoring relationships lie in the accordance to the concept of self-determination by Deci and Ryan - meeting the basic and universal needs by both partners of this interaction, namely the needs of relatedness and security, autonomy as well as competence. Becoming aware of, and taking into account these aspects may contribute to more effective and more ethical usage of tutoring in educational practice. The authors encourage detecting risk areas and factors in tutoring relationships (e.g. the risk of manipulating one's partner) in order to minimize their impact on the relationship between a tutor and a tutee, which seems beneficial to the development of both parts of tutorial interaction.